Development of challenges-based learning thematic model to improve critical thinking skills for primary school students - Nafi Isbadrianingtyas; Cholis Sa'dijah; I Wayan Dasna; Eddy Sutadji (Research and Development in Education (RaDEn), 2024)
Learning in elementary schools emphasizes receiving information and subject matter rather than developing thinking abilities and understanding concepts. However, in the 21st century which is full of challenges and rapid changes like now, students need the ability to develop critical thinking. This is a need that should be reflected in the curriculum, because individual growth is basically characterized by Critical and innovative Thinking Skills. Based on needs analysis, this research develops a learning model with a thematic challenges-based learning approach. The novelty of this research lies in the Challenges/Competition. This challenge is integrated with technology-based learning media so that students are able to think critically. The aim of this research is to produce a Thematic Challenges-based Learning model to train elementary school students' critical thinking. This research uses a Research & Development research design. Research and development, or better known as R & D, is research that produces products that can be used to overcome problems faced by practitioners in completing their tasks. This research is a development research that adopts the Ploom model. This research is a development research that adopts the Ploom model. The development process follows Akker et al (2013) development framework, which is divided into three main stages: (1) Preliminary study; (2) development and prototyping; and (3) evaluation. The data in this development research consists of qualitative data and quantitative data. The syntax of the thematic based learning challenge model includes: (1) Big Idea, (2) Thematic Integration (Webbed Model), (3) Main Question, (4) Challenge, (5) Guiding Question, (6) Guiding Activity , (7) Guiding Resources, (8) Direct experience, (9) Solutions, (10) Assessments, and (11) Publications. The advantage of the Challenges-based Learning Thematic learning model is that it can improve students' critical thinking skills because students can learn to solve problems related to everyday life.